Material selection and purchasing process / Muhamad Khairul Ikhwan Zamry - Zamry, Muhamad Khairul Ikhwan (Universiti Teknologi MARA, Perak, 2022)
Materials selection and purchasing is a process of materials management in construction. It is critical to ensuring a continuous supply of materials needed for construction purposes. It not only ensures that construction deadlines are fulfilled, but it may also save cost on a final project while preserving quality through the materials chosen and used. Nevertheless, there are currently limited appropriate guidelines for material selection and purchasing process in building projects. Therefore, this report will discuss process of material selection and purchasing during the construction of single unit house. This report was carried out at Bukit Kapar, Selangor. One of MSN Construction Sdn. Bhd projects. The objective of this report is (1) to identify the type of material involved in construction work. (2) to determine the process of material selection and purchasing and (3) to analyze the problem and solution during the material selection and purchasing process to enhance the material management process currently in use. These objectives are achieved by applying four different research methodology, observation on-site and off-site, unstructured interviews with parties involve, document reviews regarding the project, and internet browsing. Material selection and purchasing are key aspects to consider in desire to get a successful outcome in material management and provides materials at the right time, place, quantity, and quality. Inadequate material selection and purchasing, can result in unavoidable loss for a building project. To summarise, it is vital that the contractor and other parties involved cooperate in order to properly manage materials such as selection and purchasing materials in any construction. A focus on these aspects would improve material management in construction, resulting in considerably superior results.